2020
DOI: 10.3390/ijms22010003
|View full text |Cite
|
Sign up to set email alerts
|

Regulator of G Protein Signalling 4 (RGS4) as a Novel Target for the Treatment of Sensorineural Hearing Loss

Abstract: We and others have previously identified signalling pathways associated with the adenosine A1 receptor (A1R) as important regulators of cellular responses to injury in the cochlea. We have shown that the “post-exposure” treatment with adenosine A1R agonists confers partial protection against acoustic trauma and other forms of sensorineural hearing loss (SNHL). The aim of this study was to determine if increasing A1R responsiveness to endogenous adenosine would have the same otoprotective effect. This was achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…5, http://links.lww.com/MD/L407), each representing a subject category, and we obtained the subject categories clusters for the top 20 keywords. #0 CELL [21][22][23] in vitro, [24,25] mid-term around pathogenesis, [26,27] cancer, [28,29] Currently around inflammation, [28,30] injury, [31] antibody, [32,33] release, [34,35] protein signaling 16, [33,36] the latest is migration. [37,38] The most recently researched topic in the most researched discipline is corpus luteum.…”
Section: Keyword Co-occurrencementioning
confidence: 99%
“…5, http://links.lww.com/MD/L407), each representing a subject category, and we obtained the subject categories clusters for the top 20 keywords. #0 CELL [21][22][23] in vitro, [24,25] mid-term around pathogenesis, [26,27] cancer, [28,29] Currently around inflammation, [28,30] injury, [31] antibody, [32,33] release, [34,35] protein signaling 16, [33,36] the latest is migration. [37,38] The most recently researched topic in the most researched discipline is corpus luteum.…”
Section: Keyword Co-occurrencementioning
confidence: 99%
“…Adenosine is an endogenous purine nucleoside, and adenosine receptors, including A1R, A2R and A3R, are involved in the regulation of neurotransmitter release, oxidative stress responses, inflammation, blood flow, and a variety of intracellular signaling pathways including apoptosis. Activation of A1R protects inner ear hair cells, reduces hair cell death, and effectively protects against noise damage ( Kaur et al, 2016 ; Chang et al, 2017 ; Fok et al, 2020 ). Inhibition of A1R specifically was shown to cause cochlear nerve damage and to increase susceptibility to HL ( Vlajkovic et al, 2017 ).…”
Section: Co-morbidity Hypothesismentioning
confidence: 99%
“…Previous studies have shown that the “post-exposure” treatment with adenosine A 1 R agonists confers partial protection against acoustic trauma and other forms of SNHL [ 87 , 88 ]. Another study attempted to rescue noise-induced cochlear injury by post-exposure treatment targeting A 1 R without using receptor agonists [ 100 ]. This was achieved by pharmacological inhibition of the protein that regulates G protein signalling by the A 1 R (Regulator of G protein Signalling 4, RGS4).…”
Section: Regulators Of G Protein Signalling and Hearing Lossmentioning
confidence: 99%
“…Functional improvement was linked to improved survival of sensorineural tissues and afferent synapses in the cochlea. RGS inhibitors thus represent a novel paradigm for treating noise-induced cochlear injury and possibly other forms of SNHL [ 100 ].…”
Section: Regulators Of G Protein Signalling and Hearing Lossmentioning
confidence: 99%